PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. KEN LEE INDONESIA PARUNG BOGOR - Arman Syah; Angga Pratama; Islah Hadin Pratama (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
The purpose of this study was to determine the effect of motivation and work discipline on employee performance at PT. Ken Lee Indonesia Parung Bogor, either partially or simultaneously. The method used is a quantitative method. The sampling technique used was Slovin with a total sample of 83 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. The results of this study are motivation has a significant effect on employee performance with the regression equation Y = 14.019 + 0.642 X1, a correlation value of 0.709 means that the two variables have a strong level of relationship with a coefficient of determination of 50.3%. Hypothesis test obtained t count> t table or (9,054> 1,990). Thus H0 is rejected and H1 is accepted, meaning that there is a significant influence between motivation on employee performance. Work discipline has a significant effect on employee performance with the regression equation Y = 16.027 + 0.599X2, the correlation value is 0.616, meaning that both have a strong relationship with a determination coefficient of 38.0%. Hypothesis test obtained t count> t table or (7,039> 1,990). Thus, H0 is rejected and H2 is accepted, it means that there is a significant influence between work discipline on employee performance. Motivation and work discipline have a significant effect on employee performance with the regression equation Y = 8.966 + 0.480X1 + 0.300X2. The correlation value of 0.752 means that the independent variable and the dependent variable have a strong level of relationship with a determination coefficient of 55.6% while the remaining 44.4% is influenced by other factors. Hypothesis testing obtained the value of F count> F table or (52.157> 2.720). Thus H0 is rejected and H3 is accepted. This means that there is a simultaneous significant influence between motivation and work discipline on employee performance at PT. Ken Lee Indonesia Parung Bogor